Segregation Analysis of Transgenic Rice Plants CV Rojolele Harboring Cry1B Gene and Plant Selection for Potential to Yellow Stem Borer - Estiati, Amy; Sulistyowati, Yuli; Zahra, Fatimah; Nurhasanah, Ade Nena; Rahmawati, Syamsidah; S-Loedin, Inez H (ANNALES BOGORIENSES, 2012)
Transgenic rice plants harboring resistant gene to yellow stem borer, cry1B gene had been obtained. However, the cry1B gene in second generation of transgenic rice lines still segregating following Mendelian ratio 3:1. For further use in the breeding programs, it is important to ensure that the gene is dominant gene and the plants are homozygous for  cry1B gene. Selection  of homozygous transgenic rice lines containing  cry1B  gene at third, fourth and fifth generation had been conducted by PCR.  The presence of  cry1B  gene was determined by showing the PCR product of 1.9 kb. Segregation analysis proved that six transgenic rice  lines i.e. 3R7.8.15.1, 3R7.8.15.9, 3R7.8.15.10, 3R7.8.15.15, 3R7.8.15.21, 3R7.8.15.29 are homozygous lines for  cry1B  gene.   Moreover, bioassay studies at vegetative stage on six homozygous transgenic rice lines showed that  these transgenic rice lines are potential resistant to yellow stem borer comparing with non-transgenic plants, with the score of 0 (indicated no symptom) for six transgenic lines and score of9 (more than 60% damaged tillers ) for non-transgenic plants. However, to confirm the efficacy of  cry 1B  gene to yellow stem borer in naturalcondition, confined field trial in endemic area of yellow stem borer should be conducted. Keywords: bioassay, cry1B gene, transgenic rice, yellow stem borer